EFFECT OF ADDITION OF BIOTIC AND ABIOTIC ELICITORS ON ASIATICOSIDE AND MADECASSOSIDE PRODUCTION IN CALLUS CULTURE AND CELL SUSPENSIONS OF (CENTELLA ASIATICA (L.) URBAN) - Cantigi Sekar Kinasih, Nethanya
Indonesia, located along the equator, has a tropical climate and is rich in biodiversity. There are 30,000 - 40,000 plant species in Indonesia, and among them, 9,600 are identified as medicinal plants. One of these plants is gotu kola (Centella asiatica L.) which belongs to the Apiaceae family. Gotu kola has various uses and benefits, such as being an antioxidant, antitumor, immunomodulator, cardiovascular medicine, and even anti-Parkinson's agent. Additionally, gotu kola is known for its ability to heal wounds. The efficacy and benefits of gotu kola are attributed to its secondary metabolites, namely asiaticoside and madecassoside, which also act as marker compounds in gotu kola. The purpose of this research is to determine the most effective type and concentration of elicitors to enhance the compounds asiaticoside and madecassoside in gotu kola callus and cell suspension cultures. The elicitors used in this study are salicylic acid, yeast extract, and silver nitrate (AgNO3). Callus and cell suspensions were cultured in a medium containing MS + vitamins, supplemented with plant growth regulators such as 2,4-D at 2 mg/mL and BAP at 1 mg/mL, and elicitors were varied in type and concentration for a period of 15 days. The induced callus and cells were dried and extracted using a maceration method with methanol as the solvent. The content of asiaticoside and madecassoside was then analyzed using TLC (thin-layer chromatography) and TLC densitometer. In cell suspension, the addition of 2 mg/mL salicylic acid resulted in the best increase in madecassoside content, with an increase of 156.40% or equivalent to 4.223 ± 0.744 mg/mL. On the other hand, the addition of 2.5 mg/mL salicylic acid led to the highest increase in asiaticoside content, with an increase of 333.31% or equivalent to 6.504 ± 1.820 mg/mL. The addition of the three types of elicitors to the callus cultures, however, resulted in a decrease in madecassoside content by 8.26% with salicylic acid, 16.4% with yeast extract, and 23.37% with silver nitrate. As for asiaticoside, its content decreased by 52% with the addition of yeast extract and 37.16% with the addition of silver nitrate. Adding salicylic acid to the callus still provided a 5.2% increase in asiaticoside production.